Formulation and evaluation of an orally disintegrating metformin tablet using natural superdisintegrants - Jayawardhane, SW; Thuvaragan, S; Ishara Madhushani, KG; Ranasinghe, GGH; Rajitha Ranasingha, RM (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Orally Disintegrating Tablets (ODTs) provide a solution, rapidly dissolving in the mouth to improve bioavailability and compliance. Metformin is an oral hypoglycemic agent and is widely prescribed among patients with Type II Diabetes mellitus. Natural superdisintegrants: jackfruit seed starch (Artocarpus heterophyllus) and banana powder (Musa paradisiaca) are cost-effective, sustainable alternatives to synthetic superdisintegrants. Objectives: The objective of the study was to develop and evaluate orally disintegrating metformin tablets using natural superdisintegrants. Methodology: Metformin ODTs were prepared using the wet granulation method. Three formulations were developed, each containing 5% of a superdisintegrant: alkali-extracted Artocarpus heterophyllus seed starch, dehydrated Musa paradisiaca powder, and sodium starch glycolate (SSG). Tablet properties were evaluated using pre- and post-compression tests such as hardness, friability, wetting time, water absorption, disintegration, and dissolution. Drug-excipient compatibility was confirmed using Fourier Transform Infrared Spectroscopy (FTIR). Based on the post compression tests, the best formulation will be selected and subjected to a stability study at 30∘C/65% RH. A t-test was used to compare the formulations. Results: All three formulations met pharmacopeial specifications for both pre- and post-compression properties. FTIR spectroscopy confirmed the absence of any significant drug-excipient interactions in all formulations. The orally disintegrating tablet containing 5% Musa paradisiaca powder was the best formulation, exhibiting the lowest wetting time (76.33±7.77 s), disintegration time (78.00±3.6 s), and the highest water absorption ratio (106.47%±2.65%). Also, this formulation achieved a high drug release rate of 95.8% in five minutes. Statistical analysis revealed a significant difference (p<0.05) between the formulations for wetting time, water absorption ratio, and disintegration time. A three-month stability study showed that the drug content remained within pharmacopeial limits at 95.79%, confirming the formulation's stability. Conclusion: Dehydrated Musa paradisiaca powder is a potential super disintegrant for orally disintegrating metformin tablets, offering a promising and cost-effective alternative to synthetic disintegrants.
Keywords: Artocarpus heterophyllus Seed Starch; Orally Disintegrating Tablets; Natural Super Disintegrants; Metformin; Musa paradisiaca powder